Microtrabeculectomy versus Conventional Trabeculectomy in Primary Open Angle Glaucoma: A Prospective Interventional Study - Rekha Ramesh Mudhol; Ameena Shirin (Journal of Clinical and Diagnostic Research)
Introduction: Glaucoma is a group of multifactorial, irreversible, progressive optic neuropathies characterised by the loss of retinal ganglion cells. Trabeculectomy has been widely accepted as the gold-standard intervention for glaucoma for more than 30 years. A newer technique, microtrabeculectomy, was introduced to overcome the ocular complications encountered with Conventional Trabeculectomy (CT). Aim: To compare the efficacy of microtrabeculectomy with CT in treating Primary Open-angle Glaucoma (POAG). Materials and Methods: A prospective interventional study was conducted in the Department of Ophthalmology at Shri BM Patil Medical College Hospital and Research Centre (tertiary care centre), BLDE (DU), Vijayapura, North Karnataka, India, from June 2023 to August 2024. The study included 16 cases diagnosed with POAG, divided into two groups of eight patients each: Group-I- Microtrabeculectomy and Group-II- CT. Preoperative baseline characteristics were documented for all cases. They were followed-up for a three-month period to check for Intraocular Pressure (IOP) and any complications. Results: The mean preoperative and three-month postoperative IOP in Group-I was 30.75±6.04 and 13.87±2.80 mmHg, respectively, whereas in Group-II, it was 30.0±7.27 and 14.12±2.80 mmHg, respectively. The difference was statistically significant between the two groups (p<0.001). However, the differences in postoperative IOP values at the follow-ups and the differences in preoperative IOP values between both groups were not statistically significant (p>0.05). Intraoperative and postoperative complications were observed more frequently in Group-II compared to Group-I. Conclusion: Microtrabeculectomy is a safe procedure with efficacy comparable to CT for reducing IOP, while producing good filtering blebs with fewer complications.